Unit operations of particulate solids : theory and practice - Ortega-Rivas, Enrique (CRC Press, 2012)
"Preface The idea of writing this book was conceived many years ago when the author started teaching unit operations in the undergraduate program of chemical engineering at the Autonomous University of Chihuahua, even prior to attend the, then, Postgraduate School of Studies in Powder Technology at the University of Bradford. The importance, relevance and prevailing of the topic of Particle Technology remain up to date. Studies by the Rand Corporation in the 1980s identified substantial differences in the scale-up and start-up performance of plants processing powders versus those processing liquids or gases. Particularly, in 1985, the Rand Report surveyed 40 US plants and found out that start-up times were 200-300% of those predicted (compared to 20% for fluid based plants) and only achieved approximately 50% of their designed throughput. By comparison, most fluid-based processes reached 90% of planned output over the same period. Some of the reasons described on the time of the report were related to an inadequate understanding of the behavior of particle systems, which is sensitive to process scale or process history in ways that would not be expected by engineers familiar only with liquid or gas systems. The response to overcome these difficulties came in the way of promoting research, programs of study, and other activities in the field of powder or particle technology worldwide. Substantial advancements have been achieved through all these initiatives but, apparently, many of the reported reasons for these unequal understanding of powder-based processes, as compared to fluid-based processes, remain up to these days. This perception can be implied by a current need of consultancy in the subject by different types of industries worldwide"-- Provided by publisher.